Early Development of Legal Awareness and Civic Responsibility in Elementary Education - Walda Arini Nasution; Anggina Safitri; Namiroh Lubis (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Legal awareness constitutes a foundational dimension of civic character that should be cultivated from elementary school through values-based citizenship education. This study aimed to analyse the concept of legal awareness among elementary school children, examine the meaning of citizens’ rights and obligations in basic education, and identify the roles of schools, teachers, families, and instructional strategies in fostering rule-abiding behaviour. Employing a descriptive qualitative design based on library research, the study drew data from books, journal articles, legislation, and policy documents. The data were analysed through content analysis involving reduction, categorisation, interpretation, and argumentative synthesis. The findings indicate that children’s legal awareness is reflected in their ability to recognise rules, understand behavioural boundaries, and accept the consequences of their actions in everyday life. Citizenship education plays a strategic role by connecting rights and obligations with concrete practices, including discipline, cleanliness, orderly queuing, mutual respect, and compliance with school regulations. Schools strengthen legal awareness through curriculum integration, teacher role modelling, consistent rule enforcement, and habituation activities, while family support reinforces the internalisation of these values. Effective implementation is supported by a relevant civic education curriculum, an orderly school culture, and collaboration with parents, whereas limited teacher understanding, inconsistent family role models, digital media influences, and weak rule enforcement constitute major constraints. The study concludes that early legal awareness education is essential for developing discipline, honesty, responsibility, and social concern among children. These findings contribute a conceptual framework for strengthening citizenship education practices and coordinated school–family efforts to develop responsible and law-abiding citizens from an early age.